Pemberdayaan Karyawan dan Tenaga Outsourcing Terhadap Pengetahuan Protokol Kesehatan dan Perilaku Publik Terhadap Pandemic COVID-19 - Agoestina Mappadang; Melan Sinaga (LPMP Imperium, 2022)
Corona Virus 19 has resulted in high mortality rates worldwide. So knowledge of the significant impact of COVID-19 by maintaining a clean and healthy life to avoid Covid-19 is essential. In addition, the economic impact is also huge for the business sector, so many business actors are economically disturbed. The office sector is no exception as clusters of the spread of COVID-19. The purpose of the research is to get an overview of public knowledge so that they can understand the importance of community knowledge and behavior during the Covid-19 period. This research on Community Service (PKM) is qualitative with a descriptive design. The implementation of PKM is a collaboration of PT. JISS Prosperous Indonesia with Budi Luhur University. Participants in this activity were all employees and outsourced Security Officers totaling 200 people placed in offices, malls, and housing complexes. The implementation method is in the form of giving presentations and simulating health protocols and public behavior in the face of the Covid-19 pandemic. This activity results in all outsourcing personnel understanding how to maintain health protocols and community behavior in dealing with COVID-19.